Post-Traumatic Stress Disorder and Post-Traumatic Growth in Dialectical Perspective: Implications for Practice - Lushyn, Pavlo; Sukhenko, Yana (East European Journal of Psycholinguistics, 2021)
This article provides the conceptualization of the post-traumatic development (PTD) in terms of a dialectical unity of the processes of post-traumatic stress disorder (PTSD) and post-traumatic growth (PTG); practical implications for eco-centered facilitation of post-traumatic growth and development. The results of the research indicate that the process of personality development is paradoxical, irreversible and scarcely predictable. In dialectical perspective the attractor of change is not about the content of transient forms (such as trauma, success, flow) but the stabilization of their change: thesis – antithesis – synthesis. As compared to PTG, PTD’s outcome is the systemic transition to the novel (not better or positive) identity. PTSD as well as PTG constitute minor cycles within the major cycle of PTD. The core metaphor of change as personality development is the work of the immunity system (SPI) which has an ambivalent nature: on the one hand, it defends the personality from the influence of adversarial agents and on the other – proactively guards it from stagnation and lack of confrontation and discontinuity. Principals of PTD facilitation: (a) the situation of psychological help (PH) is a case of a transition to a social level of personality self-regulation; (b) an inquiry for PH contains a narrative with necessary and sufficient elements for post-traumatic growth and development; (c) these elements are objectified in paradoxes, contradictions, incongruences as the source of personality development; (d) the task of PTD facilitator is to support the explication of internal change programs by maintaining the position of ambiguity tolerance and sensitivity to accidental flow of events.